Indices of metabolic syndrome in 534 apparently healthy traders (2012)
Background: Metabolic Syndrome (MS) increases the risk of developing type-2 diabetes (DM2) and cardiovascular diseases (CVD) and it is thought to be prevalent in Nigeria. This study aims at determining the prevalence of MS and its component risk factors among apparently healthy traders in a local market in Ibadan, Nigeria. Methods: 534 apparently healthy traders from a local market in Bodija, Ibadan, Nigeria aged (18–105) years with neither DM2 nor CVD were participants of a cohort study on risk assessment of type 2 diabetes and dementia in Nigerians with metabolic syndrome. The International Diabetes Federation (2005) and the World Health Organisation (1998) criteria were used for MS and BMI respectively. Anthropometric indices (weight, height, body mass index (BMI), percentage body fat (PBF), waist and hip circumferences (WC & HC) and their ratio (WHR), waist circumference to height ratio (WHT)) and blood pressure (BP) were obtained by standard methods. Blood samples (6 ml) were obtained for the determination of glucose (FPG), total cholesterol (TC), triglycerides (TG), high density lipoprotein cholesterol (HDL-C) by enzymatic methods while low density lipoprotein cholesterol (LDL-C) was calculated. Descriptive statistics, Chi-square test and ANOVA were among the analyses conducted. Results: 301 (56.4%) of traders studied were overweight (176, 33.0%) or obese (125, 23.4%) while 17 (3.4%) and 125 (40.4%) were underweight and normal weight respectively. The prevalence of MS and obesity were 87 (16.3%) and 125 (23.4%) respectively. There was significant association between obesity and MS (p < 0.05). Both MS and obesity were significantly associated with gender (p < 0.05). The prevalence of MS and obesity was higher in female (20.9%; 31.0%) than male traders (6.5%; 7.1%) respectively. The prevalence of MS increased from normal weight (8.3%) to overweight (18.8%) to obesity (28.8%). There were significantly higher differences in age, BP(systolic and diastolic), weight, BMI, WC, HC, WHT, WHR, and PBF but lower difference in height when overweight/obese groups were compared with normal weight group (p < 0.05). TC and LDL-C were significantly higher in only obese than normal weight traders. However, FPG, TG and HDL-C were similar in all groups (p >0.05). Conclusion: There is high prevalence of MS and obesity among Nigerian traders. Female gender, hypercholesterolemia, hypertension, increasing age, general and abdominal obesity appear to be important metabolic risk factors of CVD and not DM2 among Nigerian traders. Health care strategies for effective modulation of diet and lifestyle are needed urgently. In addition, screening programs for indices of MS in all Nigerians irrespective of BMI could be considered.